Gender‐based outcomes of impeller pumps percutaneous ventricular assist devices. Issue 5 (15th October 2020) - Osman, Mohammed; Syed, Moinuddin; Abdul Ghaffar, Yasir; Patel, Brijesh; Abugroun, Ashraf; Kheiri, Babikir; Kawsara, Akram; Kadiyala, Madhavi; Balla, Sudarshan; Daggubati, Ramesh
Abstract: Background: There is paucity of data focusing on females' outcomes after the use of impeller pumps percutaneous ventricular assist devices (IPVADs). Methods: Patients who received IPVADs during the period of October 1st, 2015‐December 31, 2017, were identified from the United States National Readmission Database. A 1:1 propensity score matching was used to compare the outcomes between females and males. Results: A total of 19, 278 (Female = 5, 456; Male = 13, 822) patients were included in the current analysis. After propensity score matching and among all‐comers who were treated with IPVADs, females had higher in‐hospital major adverse events (MAEs) (38 vs. 32.6%, p < .01), mortality (31 vs. 28%, p < .01), vascular complications (3.3 vs. 2.1%, p < .01), major bleeding (7.8 vs. 4.8%, p < .01), nonhome discharges (21.6 vs. 16.3%; p < .01), and longer length of stay (7 days [IQR 2–12] vs. 6 days [IQR 2–12], p = .02) with higher 30‐day readmission rate compared to males (20.5 vs.16.4%, p < .01). Furthermore, among patients who received the IPVADs for high‐risk percutaneous coronary intervention (HRPCI), females continued to have worse MAEs, which was driven by high rates of major bleeding. However, among patients who received IPVADs for cardiogenic shock (CS) the outcomes of females and males were comparable. Conclusions: Among all‐comers who received IPVADs, females suffered higher morbidity and mortality compared to males. Higher morbidity driven mainly by higher rates of major bleeding was seen among females who received IPVADs for the hemodynamic support during HRPCI and comparable outcomes were observed when the IPVADs were used for CS.